AN INITIAL EXPLORATION INTO THE COMPARATIVE EFFECTIVENESS OF HYBRID AND TRADITIONAL STYLE TEACHING OF MICROECONOMICS - Leone, Mia Andriana (East Carolina University, 2017)
This research project aimed to explore the differences in how students learn the same material for a microeconomics course just with a different course layout. By using data previously collected from students who took Dr. Rupp’s Microeconomics course at East Carolina University (Econ 2113) hybrid and traditional style courses, we were able to use linear regression modeling to find indicators of what may impact student performance within the hybrid course. With this initial exploration of what impacts student performance within hybrid style courses, further research is necessary to completely determine what, if anything, across both styles of courses impact student performance and therefore overall learning in Dr. Rupp’s classes. It is with this in mind that this further research will be conducted in the next year and that question be answered.
Keywords: Higher education student learning; Principles of Microeconomics, hybrid learning